Hardware, methodology and applications of 2+D backscatter Mössbauer spectroscopy with simultaneous x-ray and γ-ray detection - Stamenov, Plamen (My University, 2024)
A unique method is presented for the acquisition and analysis of 57Fe backscatter Mössbauer spectra with simultaneous detection of the resonant 14.4 keV γ-rays and the characteristic 6.4 keV x-rays, using a custom-built multi-parameter analyser constructed on the basis of commercial analogue to digital converters and high-speed digital latches. The system allows for the simultaneous registration of Doppler-modulation velocities and photon energies, with up to 4096 and 8192 digital channels respectively. This arrangement is in contrast to most related systems, which detect at a single narrow energy window per detector. Samples of arbitrary atomic structure, morphology and surface topography can be studied without altering the setup or the analysis procedure, provided that the samples are at least micrometre sized. The hardware and software that are used to acquire data with minimal dead time are described and the custom and self-contained methods for post-measurement energy discrimination, background correction and velocity-axis folding are discussed. The data are fit using a general Hamiltonian model for the nuclear energy levels of 57Fe and a quantum mechanical description of the angular momentum coupling is utilised, with consideration of the crystalline and chemical disorder of the sample under examination. Three examples of distinct magnetic systems, with thicknesses ranging from 5 μ m to 6 mm, that were studied using this method are presented, these are: an amorphous CoFeB-based ribbon with ultra-soft coercivity for high-frequency applications, magnetically hard Nd-Fe-B thick films on Si substrates, examined in both as-deposited and annealed states, and a sample from the nickel-rich iron meteorite NWA 6259 that contains the atomically ordered, elevated coercivity, L 1 0 phase of FeNi, tetrataenite. The wide applicability and usefulness of this method is thus demonstrated on three distinct sample morphologies that required little to no surface preparation prior to examination.
Keywords: backscatter Mössbauer spectra; Doppler-modulation velocities; photon; ackscatter Mössbauer spectroscopy, conversion x-ray Mössbauer spectroscopy, multi-parameter analysis, energy-resolved detection, iron fluorescence, full-Hamiltonian fitting, atomic crystalline order; backscatter Mössbauer spectra; Doppler-modulation velocities; photon